Comparison of Caring Ability Between Chinese and American Nursing Students. (February 2017) - Cheng, Li; Liu, Yilan; Ke, Yuye; Wang, Wenru
This descriptive comparative study aimed to compare caring ability between Chinese and American nursing students. A survey was conducted in 544 Chinese and 109 American nursing students using Caring Ability Inventory and socio-demographic data sheet. The results indicated that the Chinese nursing students reported significantly lower scores in the Caring Ability Inventory total and three subscales ( p < .001) compared with their American counterpart. Years of program and number of siblings were factors affecting the Caring Ability Inventory scores among Chinese students ( p < .05), whereas program, marital status, prior work experience, and gender were found to influence the Caring Ability Inventory scores of American students ( p < .05). Some gaps and differences between the Chinese and America nursing students' caring ability were identified. Nurse educator should leverage the influencing factors to strengthen the caring ability of nursing students in both countries.